Designing and Equipping Sewing Training Workshops: Efficient Utilization of Equipment, Raw Materials, And Educational Resources - Khimmataliev Dustnazar Omonovich; Khidirov Urol Dobilovich; Eshankulov Ulash Doniyorovich (European International Journal of Pedagogics, 2026)
Vocational sewing education is essential for developing technical competencies required by the modern textile and apparel sectors. However, practical training environments frequently suffer from suboptimal spatial organization, inconsistent equipment utilization, and excessive raw material wastage. The absence of standardized workshop design frameworks compromises pedagogical effectiveness, increases operational expenditures, and elevates safety risks for trainees. This study develops and validates a comprehensive model for designing and equipping sewing training workshops that maximizes equipment efficiency, optimizes raw material consumption, and enhances instructional outcomes. A qualitative, descriptive, and comparative analytical approach was employed. Data were gathered through structured observations, expert interviews, and spatial mapping across twelve vocational institutions and industrial training centers. Workshop layouts, equipment deployment patterns, and material flow pathways were systematically evaluated using standardized efficiency metrics. Functional zoning aligned with ergonomic workflow principles reduced average task completion time by 22% and decreased material waste by 18%. Strategic equipment placement and standardized inventory protocols significantly improved safety compliance, minimized learning errors, and accelerated skill acquisition. Evidence-based workshop design directly enhances vocational training quality, resource sustainability, and graduate employability. The proposed model offers actionable guidelines for curriculum developers and institutional administrators, emphasizing the necessity of standardized, pedagogically aligned training environments.